Multinational Corporations and Complicity in Human Rights Violations: US Judicial Confusion - Cassel, Doug (2009)
This paper focuses on the determination of the legal liability of multinational companies, or their executives, for complicity in human rights violations committed by governments or military forces of foreign countries where they carry out their business activities. In this sense, the author reflects on the normative basis for the delimitation of this responsibility, as well as its approach in international criminal law and the jurisprudential criteria developed on the subject.